THE DISTINQUISHING FEATURES OF THE FAULTS IN THE PLATFORM COVER: RESULTS OF THE APPLICATION OF TECTONOPHYSICAL APPROACH TO THE STUDY OF THE TAMBEY HYDROCARBON DEPOSIT (YAMAL PENINSULAR) - K. Zh. Seminsky; Yu. P. Burzunova; A. I. Miroshnichenko; S. A. Bornyakov; A. A. Nezhdanov; A. V. Ershov; A. S. Smirnov; I. V. Buddo; A. K. Seminsky; A. S. Cheremnykh; I. V. Kachinskas (Геодинамика и тектонофизика, 2021)
The study was aimed to identify the features of the formation and regularities of manifestation of faults in the platform environment applying the tectonophysical approach to the study of the structure of the Tambey hydrocarbon deposit (northern Yamal), largest in the West Siberia. Such research is important in the oil and gas industry at the present stage of transition from the exploitation of declining unique and large deposits to exploration and exploitation of deposits of complex structure. The tectonophysical approach was applied consistently in three levels of research. Initial consideration was given to regular trends in the structure of the platform cover in the context of general tectonophysical ideas of disjunctive faults, their inner structure and formation features. Then, the identification of a network of large fault zones has been done at the regional level for the northern Yamal on the basis of the lineament analysis of the relief and optical modeling, three main stages of its formation have been reconstructed, and there have been identified the features of the state of stress, among other factors determining the Tambey deposit contours in three areas – western and northern Tambey and Tassyi. Finally, based on tectonophysical interpretation of 3D seismic attribute analysis data and elastoplastic modeling experiment results, for the northern Tambey area at the local level there were identified the faults zones, the features of their structures in rheologically stratified unit, and the paragenetic relationship with the regional-level structures. The study has shown that the structure of the sedimentary cover, whose formation is tectonically influenced by the adjacent mobile belts, is zone-block. It reflects the zone-block structure of the basement, though, in contrast, is not represented by narrow main-fault planes (1st-order faults). The blocks in the cover contact along rather wide zones, the inner structure of which corresponds to the early stages of faulting and is represented by a dense network of the 2nd-order fractures and faults. The fault zones are characterized by an inhomogeneous – segment – structure which is determined by an initially irregular development of deformations and complicated by rheological stratification of the sedimentary cover. Fault segments in relatively brittle rocks (sandstones) are composed of long faults whereas in more ductile (clayey) varieties these are wide parts of concentration of small faults and fractures. A style of the zone-block structure and the types of dynamic environments of its formation might be specific in different regions. The application of tectonophysical approach to the analysis of the geological-geophysical information, obtained for certain deposits, will make it possible to identify the structural conditions for hydrocarbon accumulation and migration in the sedimentary cover which is essential to choose an effective method of deposit exploitation.